Manajemen Stres Akademik pada Remaja dengan Progressive Muscle Relaxation (PMR) - Tutur Kardiatun; Surtikanti Surtikanti; Wien Fitrian R; Tri Wahyuni; Prasetyo Aji Nugraha; Dani Budiharto (Abdimas Universal, 2023)
One of the causes of stress in adolescents occurs at school.  Academic stress on students due to learning activities such as skipping school, leaving class hours prematurely, arriving late to school, collecting late assignments collected, and quitting school because they are unable to follow the learning in the chosen Department. Academic stress can lead to depression if not treated properly. Progressive Muscle Relaxation (PMR) can effectively reduce academic stress, control anxiety, and tension. The purpose of this Community Service (PkM) is to improve students’ knowledge about stress and how to manage stress with Progressive Muscle relaxation (PMR). The target of this PkM is students of Class XII Department of modeling design and Building Information (DPIB) SMKN 01 Sungai Raya, Kubu Raya, West Kalimantan. This PkM implementation method includes stress discussion and simulation of PMR techniques. The evaluation results after students perform PMR simulation obtained 41.2% feel relaxed, 26.5% feel comfortable, 20.6% feel calm, and 11.8% do not feel any change.